Case report: Management of liver cancer complicated by gastric varices rupture and bleeding: transjugular intrahepatic portosystemic shunt utilizing the mesenteric venous pathway - Sun, Guoliang; Wang, Jiangye; Zhang, Beining; Zheng, Ninggang (Frontiers in Medicine, 2024)
To avoid recurrent variceal bleeding, transjugular intrahepatic portosystemic shunt (TIPS) in conjunction with variceal embolization is considered to be an effective strategy. However, due to changes in conditions and variations in the patient's state, individuals undergoing TIPS may face challenges and limitations during procedures. The transjugular technique and combined transsplenic portal venous recanalization (PVR) with TIPS were not effective in this case due to a blocked portal vein and a previous splenectomy. With an abdominal incision, we successfully punctured the mesenteric venous system and navigated the occluded segment of the portal vein through the mesenteric approach. TIPS was then performed under balloon guidance. This study aims to explore the management of risks and complications during surgical operations and propose multiple preoperative surgical techniques to improve the success rate of the procedure.